Do We Need Taxi Counter at Major Transportation Hubs - Sulistyo Arintono (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
Taxi service at major international airport is usually an exclusive service where only those registered with the airport authority can serve passengers. Intending passengers need to register and pay a fixed fare at the taxi counter before using the service. Many customers complain that the fixed fare is significantly higher than if it was based on meter. This paper discusses the benefits or disbenefits of having taxi counter at major transportation hubs, trying to find the best solution for the benefit of all concerned parties: taxi drivers, customers and the authority. Data for analysis was obtained from observations at a number of airports and rail stations in Indonesia and Malysia. Result of the analysis suggests that it is ideal to have taxi counter, but use of the service should be made possible without having the customers to visit the counter.